Heroic life and loyalty to oneself: A reading from orteguian ratio-vitalism - Perpere Viñuales, Mora (2023)
The aim of this work is to study the concept of heroism that Ortega y Gasset presents throughout his works as a paradigmatic example of life at the service of vocation. The hero is conceived by Ortega as an individual who demands himself, who seeks to let go of habit, of the demands of the environment and of being on behalf of others, and, instead, tries to remain faithful to himself. Moreover, two characteristic notes of those who wish to carry this way of life forward are analyzed: tragedy and the sporting meaning of life.